2022
DOI: 10.33369/j.akuntansi.12.2.52-63
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy, Lifestyle, Consumption Behavior K-Pop Fans in Covid-19 Pandemic With Religiosity as Moderating Variable

Abstract: Increased consumption of Korean goods and products as well as travel to South Korea along with K-Pop which is increasingly known to the world. This consumption behavior, one of which can be seen through the lifestyle of Korean idol fans. Unfortunately, since the COVID-19 pandemic, many loss-making companies are no exception to entertainment agencies in Korea. However, the agencies that house K-pop idols are not lost their minds and are starting to build innovations by releasing a lot of content remotely. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In order to make effective use of a digital banking system, having an in-depth knowledge of the relevant technologies is essential. Nadia et al (2022) concluded that financial education and technological knowhow are the most important aspects of the banking industry. This is since the banking sector has been transformed as a result of the implementation of technology, which is why they favor financial education over financial literacy.…”
Section: Knowledge and Awareness Of Islamic Digital Bankingmentioning
confidence: 99%
“…In order to make effective use of a digital banking system, having an in-depth knowledge of the relevant technologies is essential. Nadia et al (2022) concluded that financial education and technological knowhow are the most important aspects of the banking industry. This is since the banking sector has been transformed as a result of the implementation of technology, which is why they favor financial education over financial literacy.…”
Section: Knowledge and Awareness Of Islamic Digital Bankingmentioning
confidence: 99%